The effects of aerobic, resistance, and combined exercises on the plasma irisin levels, HOMA-IR, and lipid profiles in women with metabolic syndrome: A randomized controlled trial - Aria Dianatinasab; Roghayeh Koroni; Mehrdad Bahramian; Zahra Bagheri-Hosseinabadi; Mojtaba Vaismoradi; Mohammad Fararouei; Sasan Amanat (Elsevier, 2020)
Background/objective: Irisin is suggested to be an exercise beneficial effects mediator. This study aimed to examine the effects of the aerobic exercise (AE), resistance exercise (RE), and combined exercise (CE) on the plasma levels of irisin and some metabolic and anthropometric indices. Methods: Sixty overweight women with metabolic syndrome were assigned equally into four groups: AE, RE, CE, and control. The study variables were measured before and 24 h after the intervention period. Results: None of the study groups showed statistically significant changes in the serum irisin. However, muscle mass significantly increased in the RE and CE groups. Also, a significant decrease was observed in the body fat percentage in all groups. In addition, compared with the control group, the homeostatic model assessment of insulin resistance in the AE (p = 0.021), RE (p = 0.039), and in the CE (p = 0.003) groups reduced significantly. According to the analysis of indices' changes, serum irisin was significantly correlated with the body fat percentage (r = 0.532) and HOMA-IR (r = 0.424). Conclusions: The systematic exercise program for 8-weeks did not change circulating irisin and no statistically significant difference was observed between the exercise methods. Also, serum irisin seemed to be associated with the glycemic status, body fat and weight independent of exercise activity. RCT registration code: IRCT20180806040721N2. Registry name: Iranian Registry of Clinical Trials.